Hybrid Intelligent Systems 15th International Conference HIS 2015 on Hybrid Intelligent Systems, Seoul, South Korea, November 16-18, 2015 - Abraham, Ajith; Han, Sang Yong.; Al-Sharhan, Salah A.; Liu, Hongbo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is devoted to the hybridization of intelligent systems which is a promising research field of modern computational intelligence concerned with the development of the next generation of intelligent systems. This Volume contains the papers presented in the Fifteenth International conference on Hybrid Intelligent Systems (HIS 2015) held in Seoul, South Korea during November 16-18, 2015. The 26 papers presented in this Volume were carefully reviewed and selected from 90 paper submissions. The Volume will be a valuable reference to researchers, students and practitioners in the computational intelligence field.
Extracting association rules from a retail database: two case studies -- KNN++: An Enhanced K-Nearest Neighbor Approach for Classifying Data with Heterogeneous Views -- Quantum Cryptography Trends: A Milestone in Information Security -- Human Grasp Impairment Estimation from Hand Data Glove using Bayesian Networks -- Multi-zone Building Control System for Energy and Comfort Management -- ABC+ES: Combining Artificial Bee Colony Algorithm and Evolution Strategies on Engineering Design Problems and Benchmark Functions -- System Essence of Intelligence and Multi-Agent Existential Mappings -- A Type-2 Fuzzy Concepts Lexicalized Representation by Perceptual Reasoning and Linguistic Weighted Average -- Fusion of Infrared and Visible Images Based on Object Region Detection and NSCT -- A New Ant Supervised-PSO Variant Applied to Traveling Salesman Problem -- TETS: A Genetic-based Scheduler in Cloud Computing to Decrease Energy and Makespan -- A Serious Game to make people aware of behavioral symptoms in Tourette syndrome -- Bimodality Streams Integration for Audio-Visual Speech Recognition Systems -- Similarity-based Trust Management System:Data Validation Scheme -- Reverse Engineering of Time-Delayed Gene Regulatory Network Using Restricted Gene Expression Programming -- New rules to enhance the performances of histogram projection for segmenting small-sized Arabic words -- Analyzing Genetic Algorithm with Game Theory and Adjusted Crossover Approach on Engineering Problems -- An Intelligent System For Road Moving Object Detection -- Class Imbalance Problem Using A Hybrid Ensemble Approach -- Towards multinomial classification of Neuro-Fuzzy in Digital Forensics Applications -- Multi-Agent architecture for Visual Intelligent Remote Healthcare Monitoring System -- Knowledge visualization model for intelligent dynamic decision-making -- Experimental Analysis of a Hybrid Reservoir Computing Technique -- Face recognition using HMM-LBP -- A Novel Security Architecture Based on Multi-level Rule Expression Language -- On Analysis and Visualisation of Twitter Data -- Heuristic and Exact Approach for the Close Enough Ridematching Problem -- Study on Inverse Dynamics of Full-Body Powered Pseudo- Anthropomorphic Exoskeleton Using Neural Networks -- Comparison between SAT-Based and CSP-Based approaches to resolve pattern mining problems.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence